2000
DOI: 10.1128/mcb.20.17.6435-6448.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-Dependent Binding of Yeast Heat Shock Factor to Nucleosomes

Abstract: In the nucleus, transcription factors must contend with the presence of chromatin in order to gain access to their cognate regulatory sequences. As most nuclear DNA is assembled into nucleosomes, activators must either invade a stable, preassembled nucleosome or preempt the formation of nucleosomes on newly replicated DNA, which is transiently free of histones. We have investigated the mechanism by which heat shock factor (HSF) binds to target nucleosomal heat shock elements (HSEs), using as our model a dinucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 82 publications
(96 reference statements)
2
19
1
Order By: Relevance
“…As shown in Figure 2A, the spontaneous ewe mutations have a modest effect on basal HSP82 transcription, and may even decrease it. This contrasts with the stimulatory effect of these mutations on the hsp82-DHSE1/lacZ reporter, whose promoter is assembled into a repressive dinucleosome Venturi et al 2000) and whose coding region is of bacterial origin. Therefore, the basal expression state of hsp82-DHSE1/lacZ may be sensitized to recessive mutations in genes encoding specific subunits of Mediator, possibly as a consequence of the reporter's unique chromatin structure (see Discussion).…”
Section: Glam Assaycontrasting
confidence: 42%
See 1 more Smart Citation
“…As shown in Figure 2A, the spontaneous ewe mutations have a modest effect on basal HSP82 transcription, and may even decrease it. This contrasts with the stimulatory effect of these mutations on the hsp82-DHSE1/lacZ reporter, whose promoter is assembled into a repressive dinucleosome Venturi et al 2000) and whose coding region is of bacterial origin. Therefore, the basal expression state of hsp82-DHSE1/lacZ may be sensitized to recessive mutations in genes encoding specific subunits of Mediator, possibly as a consequence of the reporter's unique chromatin structure (see Discussion).…”
Section: Glam Assaycontrasting
confidence: 42%
“…It is possible that enhanced basal expression arises from some attribute of the chromatin structure of the fusion gene, whose promoter is assembled into a repressive dinucleosome Venturi et al 2000) and whose coding region is derived from a heterologous, prokaryotic gene. Others have observed that in the context of Mediator mutations (either med16D alone or in a med5D nut2-1 double mutant), basal expression of HO/lacZ and PHO5/lacZ fusion genes is enhanced, while expression of the intact HO and PHO5 genes remains unaffected (Tabtiang and Herskowitz 1998).…”
Section: A Role For Mediator In Nucleosome Disassembly/reassemblymentioning
confidence: 99%
“…Deletion of HSE1 also obviates formation of the DNase I hypersensitive (DH), nucleosome-free region characteristic of the wild-type promoter . In place of the DH site-which, despite its accessibility, is occupied by histones under noninducing conditions (Zhao et al 2005)-are two stably positioned nucleosomes, one centered over the mutated UAS and the other centered over the core promoter (Nuc-2 and Nuc-1, respectively) Venturi et al 2000). Accompanying this structural transformation is a 100-fold drop in noninduced transcription .…”
Section: Resultsmentioning
confidence: 99%
“…We also constructed a p53-responsive reporter gene by chromosomally integrating two high-affinity PREs in place of the natural heat-shock-responsive enhancer of HSP82. The HSP82 promoter region has an intrinsically high affinity for histones Venturi et al, 2000;Zhao et al, 2005) and in the absence of ectopic p53, the PREs are assembled into a stably positioned nucleosome (schematically depicted in Figure 1b) and transcription of p53-hsp82 is virtually undetectable (Supplementary Figure 1).…”
Section: P53 Associates With the Coding Regions Of Genes It Transcripmentioning
confidence: 99%